Influence of Electrical Yield on Temperature Drop of the Photovoltaic Panel: Numerical and Experimental Findings - Filip Grubišić-Čabo; Sandro Nižetić; Ivo Marinić Kragić; Tonko Garma (Journal of Sustainable Development of Energy, Water and Environment Systems, 2020)

(untitled)
This manuscript deals in confirmation of drop in photovoltaic panel temperature under load. Two panels are compared, one with the load and other without the load. The panel under load should have larger heat dissipation (i.e. be cooler), when electrical yield is taken as an outgoing heat flow. During the experiment, a thermovision of the panels under solar irradiance was made with the thermal camera. Results of the first case show only minor change in panel temperature. Results of the second case, where one panel is under load, show reduced temperature of loaded panel, by up to 4 °C. Previously developed numerical model is updated with the measured data in the experiment. A measured electrical yield is taken into the account when the solar irradiance was modelled. Numerical model confirms the temperature drop and corresponds with infrared thermography data. Gained results can help in design of the photovoltaic systems, where more variants of operating conditions can be used in order to keep the panel on desired operating temperature.